Implementation of Program Islamic Religious Education Program at State Junior High School (SMPN) 2 Kuta Makmur, Aceh Utara - Muhammad Hatta (Journal of Educational Analytics, 2023)
The flagship Islamic religious education program is a collaboration between the Aceh provincial government and the Aceh Regional Ministry of Religion. This program is intended to create excellence in PAI learning. The purpose of this study was to find out the implementation of the superior Islamic religious education program at SMPN 2 Kuta Makmur, North Aceh. The research method used is a qualitative research method. Data collection techniques used are interviews and observation. Furthermore, the data were analyzed using a qualitative descriptive analysis. The results of the study show that in practice the leading Islamic religious education program at SMPN 2 Kuta Makmur Aceh Utara is carried out by strengthening Guidance to Write and Read the Qur'an (BTQ) so that students become a Qur'anic generation. The implementation of the program begins with outreach to all school members. Obstacles faced in implementing this superior Islamic religious education program include the lack of operational costs and the lack of facilities owned by schools.